Ecological features of the Caspian Sea region with different legal and economic mode - G. A. Monahova; G. M. Abdurahmanov; L. Z. Murzakanova (Юг России: экология, развитие, 2015)
Set of new positions and conclusions about ecological features Caspian Sea areas with the various legal and economic mode, of interest for scientific maintenance of steady development and a favorable environment of the Caspian region is considered.